Perichoretic Persons: Diagramming Augustine's Mental Trinity - Adams, Nathan A. (Perichoresis, 2025)
This article seeks to develop new insight from De Trinitate into what it means to be a trinitarian person by diagramming the interchange of cognition and love that Augustine traces in the mental trinity. It begins with some important groundwork by Augustinian scholars that enriches the formula that persons are relations. Then, we review how Augustine used "Eastern" themes of interpenetration and interchange to describe the life of the divine persons, themes later to be termed perichoretic. This leads to consideration of the interesting subject of movement or logical priority in God. Finally, we move into original research by diagramming the mental trinity, that is, tracing the trinitarian movements inherent in the nature of knowing and loving and considering how this might apply to each divine person if God is indeed sapientia and charitas. We will consider that Augustine may have conceived of the interchange of the life of the triune persons extending even to the enjoyment of a shared cognition. If this is plausible, then the mental trinity provides much more insight into what it means to be a divine person than is commonly attributed to him – insight which could be productively deployed in contemporary trinitarian theology.